Reinterpreting Li Brocade Patterns: A Cultural Narrative Approach to Themed Hotel Design and Identity Enhancement - Wu, Shengze; Inkuer, Akapong; Mayusoh, Chanoknart; Suwannatat, Permsak (Journal of Cultural Analysis and Social Change, 2026)
In the context of the revitalization of intangible cultural heritage, this study systematically explores the innovative application path of Li brocade patterns in experiential hotel spaces, aiming at the problem of weak identity perception caused by the surface application of Li brocade patterns in hotel design. Based on the theory of spatial narrative, combined with pattern genealogy analysis and design practice, a theoretical model of "pattern deconstruction-semantic fusion-scene symbiosis" is constructed, while shaping an immersive spatial experience with national memory. The study constructs a theoretical framework of "symbol extraction-spatial encoding-experience generation" for intangible cultural heritage elements, providing a methodological reference for the value transformation of traditional culture in contemporary accommodation space.